Integrated Briefcase Model: A Teaching Aid in the Practicum of Digital Electronics - Mashoedah Mashoedah; Umi Rochayati; Muhammad Munir (LPPM UNY, 2013)
This study is aimed at designing as well as producing an integrated briefcase model as a teaching aid in the teaching of digital electronics practicum and its feasibility. This study can be classified as research and development study. It was conducted in the Electronics Engineering Education Department and State Vocational School 2 Yogyakarta. The teaching aid was developed through: conducting needs analysis, designing, implementing, and testing. The testing was carried out twice covering the performance and feasibility. The data were collected by using questionaires distributed to the users. The students of SMK Negeri 2 Yogyakarta were the subjects of the research. In this study the data were analyzed descriptively. The study findings showed that the teaching aid could be realized and meet the competence required in the digital electronics subject. The score obtained from the content validity test was 90% (categorized as very feasible). The score of the material validity was 80% (categorized as feasible). The score of the feasibility in terms of the material aspect was 42% (categorized as feasible). The technical aspect was scored 69.83% (categorized as feasible).